The Growth Performance of Micropropagated Talasbanana (Musa paradisiaca var. sapientum L) Seedlings Cultivated on Peatlands - Fakhrur Razie; Chatimatun nisa; Nofia Hardarani (Journal of Wetlands Environmental Management, 2017)
ABSTRACTTalas banana (Musa paradisiaca var. sapientum L.) has a high economic value. However, because of slowly breeding, a quick way of propagation: i.e. in vitro is required.Peatlands inSouth Kalimantan are quite large and has potential to be used for planting area of Talas banana. The acclimatization of seedlings planted on the peatsrequires more fertilizers, considering the low nutrient content of the peats. This study aims to determine the chicken manure and nitrogen-phosphor-potassium (NPK) fertilizer on the growth of Talasbanana acclimatized in peatlands. This study applied a randomized block design (RBD) factorial: (1) the amount of chicken manure (K), namely: k1 = 5 t ha-1; k2 = 10 t ha-1; k3 = 15 t ha-1; k4 = 20 t ha-1, and (2) the amount of NPK fertilizers (P), namely: p1 = 200 kg ha-1; p2 = 250 kg ha-1; p3 = 300 kg ha-1. Therefore, 12 treatments. DITAMBAHKAN TERDAPAT 12 PERLAKUAN. All treatments have 3 replicates. The results of the experiment showed that there was no interaction between doses of chicken manure with NPK. The amount of chicken manure 5 t ha-1 resulted in the highest increment of plant height observed at 2nd, 4th, 6th, 8th, 10th and 12thweek after planting, increment of stem diameter, addition of leaf number, width and length of leaves.The results of experiment also revealed that the best increment of plant height observed at 8th week after planting and stem diameter observed at 4th week after planting was obtained by 250 kg ha-1of NPK fertilizer application. KOMBINASI TIDAK BERPENGARUHKey-word: propagation; in vitro; peatlands; chicken manure; Talas banana